Innovation in collaborative design: an exploratory study in hackathon. Issue 2 (3rd April 2021) - Lobbe, Justine; Bazzaro, Florence; Sagot, Jean-Claude
ABSTRACT: Collaborative design is the use of design practices which tend to favor the integration of different experts, and to support creativity and innovation. Therefore, in this study, we were particularly interested in the collaborative design tools used in the specific context of a pedagogical hackathon. During this event, 1310 engineering students mentored by professors and industrial experts worked on around 131 industrial projects. In this article, we will present our study of the tools put in place by the participants of these innovative projects according to their training. Our study is based on a collection of project data. We will show that storyboards are often used in projects that tend toward radical innovation. Moreover, these tools are used by groups who have not received specific training on using storyboards.